Liquidity characteristics of large and small rubber products manufacturing firms in Malaysia / Umi Kalthom Hamdan - Hamdan, Umi Kalthom (1993)
The main purpose of this project paper is to study the size-liquidity relationship of small and large rubber products manufacturing fijms in Malaysia for the period 1986 to 1990. It also investigates the assessibility of finance for the small and large firms. In addition, it determines the impact of the liquidity position to the firms' availability of finance.